WHAT ARE THE BELLS RINGING FOR?! – A CONTRIBUTION TO UNDERSTANDING DEPENDENCE OF THE PANDEMIC AND GLOBAL TRADE - Malovic, Marko G; Petrović, Vesna (Poslovna ekonomija, 2022)
ABSTRACT: The outburst of COVID-19 pandemics has heavily contracted and structurally altered both the size and the flows of international trade through 2020 and 2021. Even though contagion effect on global trade is clearly a negative one for a number of reasons elaborated in the paper, we venture to argue that this is in fact an evolutionary, expected and unavoidable consequence of the very globalisation process. Among the key trends affecting the present and future of the international trade, roughly half of them are fully independent and the other half at best semi-dependent from the pandemics itself. In other words, it appears that the bell tolls for the wrong suspect, in as much as the two phenomena might be cointegrated, not to mention the ideological and operational confusion behind recently widespread deliberations to deploy trade policies in order to simultaneously achieve several non-trade objectives of dubious compatibility. Notwithstanding the grim clouds ahead and above, some Mediterranean economies -if prove able and flexible enough- may yet turn out to be the unintended winners of the silver lining.
Keywords: COVID-19, International Trade, (De)Globalisation, Global Supply Chains